Enhanced Aqueous Solubility and Antibacterial Activity of Cefuroxime Axetil - Salam , Moushumi Tabassoom; Kumar , Ashim; Barman, Ranjan Kumar (Challenges and Advances in Pharmaceutical Research Vol. 4, 2022)
The objective of this investigation was to improve the solubility and consequent antibacterial activity of cefuroxime axetil (CA), a \(β\) -lactamase-stable broad spectrum second generation cephalosporin through solid dispersion (SD) technique. CA loaded SDs (CSDs) were made using a solvent evaporation process with various amounts of microcrystalline cellulose (MCC) as a carrier. The characterization of CSDs was done by in-vitro dissolution study, thermal analysis (DSC), crystallinity (PXRD), interactions (FTIR) and morphology (SEM). With a drug-carrier (CA: MCC) ratio of 1:3, CSD-2 had the highest solubility rate among the formulations, 2.59 fold stronger than pure CA. DSC, PXRD, FTIR, and SEM investigations confirmed that the increased dissolution rate was due to drug conversion from crystalline to amorphous form during SDs production. Antibacterial activity of CSD-2 against Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) showed 1.94- and 6.75-fold higher relative zone of inhibition (RZOI), respectively than pure CA. In terms of improved dissolving rate and antibacterial activity, CSD-2 has been proven to be the most effective optimized formulation. As a result, it could be a promising alternative to traditional CA dosage formulations. Before proposing it as a novel formulation, more research is needed to evaluate its pharmacokinetic features, in-vivo antibacterial activity, and safety.